Nanozymes expanding the boundaries of biocatalysis - Ruofei Zhang; Xiyun Yan; Lizeng Gao; Kelong Fan (Nature Communications)
Abstract Biocatalysis is fundamental to biological processes and sustainable applications. Over time, the understanding of biocatalysis has evolved considerably. Initially, protein enzymes were recognized as the primary biocatalysts due to their high catalytic efficiency under mild conditions. The discovery of ribozymes expanded the scope of biocatalysts to include nucleic acids and the development of synthetic or semisynthetic artificial enzymes sought to overcome the limitations of natural enzymes. The emergence of nanozymes, nanomaterials with intrinsic biocatalytic activity, has further broadened this field. Nanozymes possess abundant active sites, multiple active phases, and nanostructures that maintain stability even under extreme conditions, along with unique physicochemical properties. These attributes enable nanozymes to perform efficient biocatalysis in diverse forms and under a wide range of conditions. The discovery of natural biogenic nanozymes, such as magnetosomes, ferritin iron cores, and amyloid protein assemblies, underscores their potential physiological functions and roles in disease pathogenesis. This review explores the distinct properties and catalytic mechanisms of nanozymes, elucidates their structure-activity relationships, and discusses their transformative impact on biocatalysis, highlighting their potential to reshape fundamental concepts and practical applications in the field.